Self-Efficacy Weight Management and Family Support on Risk Factors of Prediabetes Patient - Martines, Krisna Rina; Prabawati, Dewi; Supardi, Sudibyo (Journal of Nursing Science Update (JNSU), 2023)
The shift in the pattern of non-communicable diseases to a younger age makes prediabetes undetected and tends to be ignored. Monitoring weight is an essential behavior for individuals to reduce the risk of obesity as a predictor of prediabetes. In addition, family support plays a crucial role in maintaining each individual's health in deciding his lifestyle. This study aimed to determine the relationship between self-efficacy weight management (SEWM) and family support on risk factors for prediabetes at the Community Health Center, Batam. The research design is a descriptive correlation with the cross-sectional approach. Fifty respondents were chosen using a purposive sampling technique based on the inclusion and exclusion criteria. Instrument of INA-PRISC questionnaire, Weight Efficacy Lifestyle Short Form Questionnaire, and Perceived Social Support from Family (PSS- Fa) utilized in this study. Based on univariate results, the majority of respondents aged 26-35 years (30%), female (68%), higher education background (78%), obesity (>25) (80%), had a family history of DM (60%), not smoking (70%), physical activity <150 minutes/week (94%), hypertension >160/100 mmHg (44%), moderate risk of prediabetes (48%), low SEWM (70%), and good family support (38%). A bivariate statistical test using Kendall's Tau B revealed there was a significant relationship between SEWM (< 0.05) and family support for risk factors for prediabetes (< 0.05). It is suggested that respondents increase self-awareness in the early detection of prediabetes risk and the family's active role in assisting family members in starting an active and healthy lifestyle.